Laboratory and clinical significance of rare antiphospholipid antibodies in preeclampsia patients : a preliminary study by Mimi Azreen Abdullah - Abdullah, Mimi Azreen (2015)
Preeclampsia (PE) continues to cause mortality and morbidity in pregnancy. Antiphospholipid antibody (APA) is known to induce proinflammatory and prothrombotic mechanisms. Relationship between PE and APA was first suspected due to high rate of PE in women with antiphospholipid syndrome (APS). It is not known whether rare types of APA are present in PE patients especially in our populations. The aim of our study is to detect antiannexin V (antiAnV) and antiphosphatidyl inositol (aPI) antibody in PE patients. A cross sectional study was done at HSIJB and HUSM from January 2013 to December 2014. Eighty four samples were collected with equal number of PE and non PE and analyzed for FBC, coagulation, biochemical profiles and antiAnV and aPI. These antibodies were analyzed using ELISA method. AntiAnV IgG was persistently detected in one case of severe PE associated with twin pregnancy during pregnancy and 5 months postnatal period. No other antibodies were detected. This positive case was diagnosed with early onset PE and had preterm delivery at 33 weeks gestation due to severe PE. Her activated Partial Prothrombin Time (aPTT) was shortened (19 sec) in keeping with our finding of significant different aPTT between mild and severe PE (p = 0.007). APA was not detected in other PE patients and non PE. However, there was a significant different of aPI IgM concentration between PE and non PE. The association with APS is uncertain as it is IgM type. However, the presence of IgM in pregnancy even as a transient antibody could be of clinical significance as this is related to immune derangement during pregnancy period and may lead to PE development. From this study, the prevalence of rare types of APA in PE patients is low (2.4%). However, larger studies are needed for more accurate data and to include more APA for better correlation and understanding of the disease. Other clinical outcomes need to be evaluated in order to provide better management of PE so that the maternal and fetal morbidity and mortality can be minimised. Shortened aPTT in severe PE is a significant finding and need to be explored especially in PE patients with positive for APA.